2019
DOI: 10.3390/w11010117
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Water Wells Efficiency Reduction and Ageing Process Compensation

Abstract: Water wells play an increasingly important role in providing water for the civilian population all over the world. Like other engineering structures, wells are subject to ageing processes resulting in degradation, which is observed as a reduction in hydraulic efficiency throughout their lifespan. To date, it has been found that the ageing process of a well is determined by a number of factors. The mathematical description of this process can be simplified. Drawing on Jacob’s equation, this paper presents the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The bed and side walls were insulated with a synthetic insulation material geo-membrane thickness of 1.0 mm, which was designed, tested, and approved in accordance with American Society for Testing and Materials specification number D 1004, D 1238, D 1505, and D 1603, where it was tested in the Construction Research Institute (CRI) of NWRC [13], and the pond is depicted as shown in figure (5).…”
Section: Figure (4): Pond Design and Dimensionmentioning
confidence: 99%
“…The bed and side walls were insulated with a synthetic insulation material geo-membrane thickness of 1.0 mm, which was designed, tested, and approved in accordance with American Society for Testing and Materials specification number D 1004, D 1238, D 1505, and D 1603, where it was tested in the Construction Research Institute (CRI) of NWRC [13], and the pond is depicted as shown in figure (5).…”
Section: Figure (4): Pond Design and Dimensionmentioning
confidence: 99%